2003
DOI: 10.1097/01.pcc.0000043293.83440.79
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically ventilated pediatric stem cell transplant recipients: Effect of cord blood transplant and organ dysfunction on outcome

Abstract: Pediatric recipients of an umbilical cord blood transplant who subsequently required mechanical ventilation had lower pediatric intensive care unit and hospital survival rates compared with patients receiving bone marrow transplantation. Survival at 2 yrs for umbilical cord blood transplant and bone marrow transplant patients was similar. Predictors of outcome for all stem cell transplant recipients requiring mechanical ventilation included pediatric intensive care unit diagnosis requiring intubation and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…On the other hand, survival to hospital discharge in mechanically ventilated patients improved from 9 to 11% pre-2000 to 28% in one study describing their experience after 2000. 39 Factors associated with poor prognosis in pediatric SCT patients admitted to the ICU are similar to what has been described for adult patients (see above, Tables 3 and 4) and include the presence of respiratory failure, increased duration of mechanical ventilation, MOSF, need for renal replacement therapy (hemodialysis, ultrafiltration, or the combination), hepatic toxicity, neurologic deterioration, gross hemorrhage, the presence of GVHD and a high O-PRISM score. The acronym stands for the oncological pediatric risk of mortality scale that is a well-recognized scoring system used in the pediatric oncology patient.…”
Section: Limitations Of the Published Experiences: Adultsmentioning
confidence: 60%
See 2 more Smart Citations
“…On the other hand, survival to hospital discharge in mechanically ventilated patients improved from 9 to 11% pre-2000 to 28% in one study describing their experience after 2000. 39 Factors associated with poor prognosis in pediatric SCT patients admitted to the ICU are similar to what has been described for adult patients (see above, Tables 3 and 4) and include the presence of respiratory failure, increased duration of mechanical ventilation, MOSF, need for renal replacement therapy (hemodialysis, ultrafiltration, or the combination), hepatic toxicity, neurologic deterioration, gross hemorrhage, the presence of GVHD and a high O-PRISM score. The acronym stands for the oncological pediatric risk of mortality scale that is a well-recognized scoring system used in the pediatric oncology patient.…”
Section: Limitations Of the Published Experiences: Adultsmentioning
confidence: 60%
“…The pediatric UCBT patient Three reports have described ICU transfer in the pediatric UCBT recipient, 36,39,41 although two provide very limited information on a small number of patients. 36, 41 Hagen et al 39 described the clinical course for 98 ICU admissions over a 9-year period; 52 of their subjects received an UCBT and 34 underwent BMT.…”
Section: Limitations Of the Published Experiences: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 One paediatric study has also demonstrated a difference in prognosis with different sources of stem cells. 19 Despite these concerns, children and adults undergoing HSCT continue to be admitted to ICUs. Most published data concern adult oncology patients undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in both adult and pediatric patients have analyzed the outcomes of BMT and PBSCT patients requiring ICU expertise or mechanical ventilation. [4][5][6][7][8] However, adult UCBT recipients may have different critical care needs and outcomes than BM and PB transplant patients due to different preparative regimens and infusion of lower numbers of hematopoietic stem cells than BM or PB recipients. 9 To our knowledge, there have been no published studies of adult patients receiving UCBT and requiring ICU support.…”
Section: Introductionmentioning
confidence: 99%